Study of Maudhu'i's Interpretation of Secularism Verses - Asy Syifa Dhea Salsabila; Azzahra Tsabithania Arifiy; Chyntia Nursyifa Fitri (Bulletin of Islamic Research, 2023)
In this modern era, the Islamic religion is faced with various kinds of complex problems. The values of the Islamic religion have begun to fade and religious rules are put aside in order to fulfill one's desires. Secularism is a phenomenon that comes from evidence of humanity's distance from Islamic teachings. The perpetrators of secularism do things that are deviant for the good of their world so that their desires are fulfilled while religious values are not adhered to. This also happened during the time of the Prophet Muhammad SAW, when the world became their goal and they underestimated the affairs of the afterlife. The aim of this paper is to understand the concept of secularism in the verses of the Koran using a Maudhu'i interpretation approach. The method used is a qualitative method using literature review. There are several verses in the Qur'an that discuss secularism, namely Q.S Al-Baqarah verses 85-86, Q.S Hud verses 15-16 and Q.S Al Isra verse 18, at-Tin verse 4, ar-Rum verse 30, and an-Nisa verse 119. As a form of interpretation using a maudhu'i approach, the researcher also discusses asbab al-nuzul, munasabah and language rules as a complement to the interpretation. Beside that, it also mentions the phenomena of secularism in the modern era such as plastic surgery and sex change. The results of the research explain that secularism is an ideology that is contrary to Islam. Where this concept separates religious involvement in worldly matters and leding to atheisme in the end.